Strategies of content knowledge representation and EFL learners‘ english writing proficiency: Mediating role of critical thinking skills - Shen, Xiaolei; Ismail, Lilliati; Hu, Yurong; Wei, Mengqi (Center for Open Science, 2023)
The exploration of optimizing content knowledge representation and enhancing critical thinking capabilities in English as Foreign Language (EFL) learners’ writing still needs to be improved. Cultivating adept critical thinking skills and effective content knowledge representation is paramount for EFL learners, given its correlation with heightened writing proficiency. This study sought to examine critical thinking skills as a mediator in the correlation between strategies of content knowledge representation and writing proficiency among EFL learners. A total of 360 English as foreign language participants engaged in the California Critical Thinking Skills Test and responded to a questionnaire on strategies of content knowledge representation conducted at Kaifeng Science Technology and Communication College, China. Subsequently, participants undertook a writing task, and the outcomes underwent analysis using SPSS 26.0, incorporating descriptive analysis, correlational analysis, and AMOS 24.0 for mediating analysis. The findings unveiled a correlation between critical thinking skills and EFL learners’ writing proficiency, echoing the association observed between content knowledge representation strategies and writing proficiency. Furthermore, critical thinking skills were identified as a mediator, linking content knowledge representation strategies to writing proficiency among EFL learners. The combination of content knowledge representation and critical thinking skills emerged as a positive role in the writing process. This research underscored the paramount significance of critical thinking skills within a specialized discipline, highlighting their transformative potential for EFL learners’ writing competency and accentuating their functions in the broader writing pedagogy.